Impact of fluvoxamine on outpatient treatment of COVID-19 in Honduras in a prospective observational real-world study - Pineda, Estela; Singh, Jarmanjeet; Pineda, Miguel Vargas; Umanzor, Jose Garay; Baires, Fernando; Benitez, Luis G.; Burgos, Cesar; Sekhon, Anupamjeet Kaur; Crisp, Nicole; Lewis, Anita S.; Radwanski, Jana; Bermudez, Marco; et al. (Frontiers in Pharmacology, 2022)
Background: The COVID-19 pandemic has impacted millions of lives globally. While COVID-19 did not discriminate against developed or developing nations, it has been a significant challenge for third world countries like Honduras to have widespread availability of advanced therapies. The concept of early treatment was almost unheard of when early outpatient treatments utilizing repurposed drugs in Latin American countries began showing promising results. One such drug is fluvoxamine, which has shown tremendous potential in two major studies. As a direct result, fluvoxamine was added to the standard of care in a major medical center outpatient COVID-19 clinic. Methods: This is a prospective observational study performed at the Hospital Centro Médico Sampedrano (CEMESA) in San Pedro Sula, Cortes, Honduras in the COVID-19 outpatient clinic. All patients were at least 15 years of age who had presented with mild or moderate signs and symptoms of COVID-19, and who also had a documented positive SARS-CoV-2 antigen or Reverse Transcription Polymerase Chain Reaction (RT-PCR) were included in the study. These patients then were all prescribed fluvoxamine. The cohort of patients who decided to take fluvoxamine were compared for primary endpoints of mortality and hospitalization risk to the cohort who did not take fluvoxamine. Patients were then monitored for 30 days with the first follow up at 7 days and the second follow up at 10–14 days of symptom onset. Categorical variables were compared by Pearson Chi-square test. The Relative risk was calculated using regression models. Continuous variables were compared by t-test and Wilcoxon rank-sum tests. Results: Out of total 657 COVID-19 cases, 594 patients took fluvoxamine and 63 did not take fluvoxamine. A total of five patients (0.76 percent) died, with only one death occurring in the fluvoxamine group. Patients who received fluvoxamine had a significantly lower relative risk of mortality (RR 0.06, p 0.011, 95% CI 0.007–0.516). There was a lower relative risk of hospitalization in the patients who in the fluvoxamine group. (−10 vs. 30 hospitalizations, RR 0.49, p = 0.035, 95% CI 0.26–0.95). There was 73 percent reduction in relative risk of requiring oxygen in the fluvoxamine group (RR 0.27, p < 0.001, 95% CI 0.14–0.54 Mean lymphocytes count on the first follow-up visit was significantly higher in the fluvoxamine group (1.72 vs. 1.38, Δ 0.33, p 0.007, CI 0.09–0.58). Conclusion: The results of our study suggest that fluvoxamine lowers the relative risk of death, hospitalization, and oxygen requirement in COVID 19 patients.